Structural and Enzymatic Characterization of ABgp46, a Novel Phage Endolysin with Broad Anti-Gram-Negative Bacterial Activity - Oliveira, Hugo; Vilas Boas, Diana; Mesnage, Stéphane; Kluskens, Leon D.; Lavigne, Rob; Sillankorva, Sanna; Secundo, Francesco; Azeredo, Joana (Frontiers in Microbiology, 2016)
The present study demonstrates the antibacterial potential of a phage endolysin against Gram-negative pathogens, particularly on A. baumannii multidrug resistant strains. We have cloned, heterologously expressed and characterized a novel endolysin (ABgp46) from Acinetobacter phage vb_AbaP_CEB1 and tested its antibacterial activity against several multidrug-resistant A. baumannii strains. LC-MS revealed ABgp46 is an N-acetylmuramidase, that is also active at a broad pH range (4.0-10.0) and up to 50°C. Interestingly, ABgp46 has intrinsic and specific anti-A. baumannii activity, reducing up to 2 logs of multidrug resistant strains, in a 2 hour-time frame. By combining ABgp46 with several organic acids that act as outer membrane permeabilizing agents, it is possible to increase and broaden its antibacterial activity to other Gram-negative bacterial pathogens. Especially in the presence of citric and malic acid, ABgp46 reduces A. baumannii below detection limit (> 5 log) and more than 4 logs P. aeruginosa and Salmonella Typhimurium strains. Overall, this globular endolysin presents a broad and high activity against Gram-negative pathogens, that can be enhanced in presence of citric and malic acid, and be used in human and veterinary medicine.